2003
DOI: 10.1063/1.1611274
|View full text |Cite
|
Sign up to set email alerts
|

Electron-beam-induced deposition using a subnanometer-sized probe of high-energy electrons

Abstract: Articles you may be interested inInvestigation of morphological changes in platinum-containing nanostructures created by electron-beam-induced deposition J. Spatial resolution limits in electron-beam-induced deposition J. Appl. Phys. 98, 084905 (2005); 10.1063/1.2085307Position-and size-controlled fabrication of iron silicide nanorods by electron-beam-induced deposition using an ultrahigh-vacuum transmission electron microscope Mechanisms of nano-hole drilling due to nano-probe intense electron beam irradiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
85
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(87 citation statements)
references
References 14 publications
(6 reference statements)
2
85
0
Order By: Relevance
“…Tungsten hexacarbonyl (W(CO) 6 ) powder was used as a precursor, of which the vapor pressure is approximately 2 Pa at room temperature. The precursor has been proved to be suitable for fabricating nano-sized structures on conductive substrates 1,3,5,7) as well as on insulator substrates 9,10) with EBID. Crystalline SiO 2 thinfilm specimens suitable for TEM observation were used as substrates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tungsten hexacarbonyl (W(CO) 6 ) powder was used as a precursor, of which the vapor pressure is approximately 2 Pa at room temperature. The precursor has been proved to be suitable for fabricating nano-sized structures on conductive substrates 1,3,5,7) as well as on insulator substrates 9,10) with EBID. Crystalline SiO 2 thinfilm specimens suitable for TEM observation were used as substrates.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the controllability of the beam, zero, one, two, or three dimensional small-sized objects have been fabricated. [1][2][3][4][5][6][7][8] Conductive substrates are generally used in these fabrications, because they provide stable fabrication conditions. Recently, by using insulator substrates, Al 2 O 3 , nanometer-sized (nano-sized) tungstenstructures (W-structures), namely, wire-like, dendrite-like and tree-like W-structures, have been fabricated with EBID using a precursor W(CO) 6 in a 200 kV transmission electron microscope.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of nanometer-sized structures have been fabricated [1][2][3]. Due to stable fabrication, electric conductive substrates are generally used [3] and compact structures are usually fabricated.…”
mentioning
confidence: 99%
“…Still, although CVD deposits are often more pure, the advantage of using the FIB system it its ability for precise, localized deposition, and its capacity for controlling the different heights of the depositions. Even so, the use of ion beams may not always be ideal; research has shown that in certain cases, electron nanofabrication has been able to match the work of the ion beam without the impurities that come along with using the FIB [9].…”
Section: Depositionmentioning
confidence: 99%
“…We look into the ever advancing field of integrated circuits and discuss how the FIB can be used for defect analysis as well as structure modification. We also consider 9. Focused Ion Beam System-a Multifunctional Tool for Nanotechnology 249…”
mentioning
confidence: 99%